2022
DOI: 10.26832/24566632.2022.0703016
|View full text |Cite
|
Sign up to set email alerts
|

Shifting from paddy production for aquaculture: An economic study in a selected area of Bangladesh

Abstract: Shifting rice cultivation to aquaculture is a burning issue of agricultural land use policy in Bangladesh. The study was conducted to identify the reasons for change the paddy farming to fish culture and relative profitability of both enterprises randomly selected 50 sample farmers from Mymensingh district in Bangladesh. Primary data were collected through field survey. Mostly tabular analysis was done to achieve the objectives. To determine the net return of fish and rice production, profitability analysis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…This shift is driven by factors such as erratic rainfall, fluctuations in temperature, a shortage of labourers, limited economic benefits, and difficulties in accessing agricultural inputs [56]. Relative profitability, labour shortages, and low land topography are the key determinants of converting rice fields into aquaculture farming in the districts of Mymensingh and Khulna [57][58][59]. Shortage of labour and low price of rice also discourage farmers from growing rice instead of other crops.…”
Section: Plos Onementioning
confidence: 99%
“…This shift is driven by factors such as erratic rainfall, fluctuations in temperature, a shortage of labourers, limited economic benefits, and difficulties in accessing agricultural inputs [56]. Relative profitability, labour shortages, and low land topography are the key determinants of converting rice fields into aquaculture farming in the districts of Mymensingh and Khulna [57][58][59]. Shortage of labour and low price of rice also discourage farmers from growing rice instead of other crops.…”
Section: Plos Onementioning
confidence: 99%
“…One of the most significant inputs in the fish farming industry is labor (Ahmed, 2007). Study suggested that, most of labors are involved in pond management and feeding application works, while some of them are engaged with the security purpose, chemical application, and harvesting procedure (Ahmed, 2007;Asad et al, 2022;Jahan et al, 2021;Meah and Akther, 2021;Rahman et al, 2022;Saha et al, 2004;Sujan et al, 2021). However, the labor cost might be different due to geographical locations, availability, price of food, demand and supply, economic and food inflation (Guha and Tripathi, 2014;Taghizadeh-Hesary et al, 2019).…”
Section: Human Labor Costmentioning
confidence: 99%
“…Different types of land use decisions are more common among small farmers (Islam et al, 2020). The transition from rice farming to aquaculture is a subject of ongoing deliberation within the agricultural land usage policy of Bangladesh, which has the potential to impact the farmers' capacity to enhance the array of their income sources (Rahman et al, 2022). Farmers' perceptions of profitability, amount of land owned, level of education, annual income, and farming experience are all important considerations when making the switch from rice cultivation to smallscale aquaculture (Anisuzzaman et al, 2015;Rasel, 2016).…”
Section: Introductionmentioning
confidence: 99%